Azathioprine and Mycophenolate Mofetil Adherence Patterns and Predictors Among Medicaid Beneficiaries With Systemic Lupus Erythematosus. Issue 11 (29th October 2019) - Feldman, Candace H.; Collins, Jamie; Zhang, Zhi; Xu, Chang; Subramanian, S. V.; Kawachi, Ichiro; Solomon, Daniel H.; Costenbader, Karen H.
Abstract : Objective: Azathioprine (AZA) and mycophenolate mofetil (MMF) are immunosuppressants frequently used in the treatment of moderate‐to‐severe systemic lupus erythematosus (SLE). We studied longitudinal patterns and predictors of adherence to AZA and MMF in a nationwide US SLE cohort. Methods: In the Medicaid Analytic eXtract (2000–2010) database, we identified patients with SLE who initiated AZA or MMF (no use in the prior 6 months) with ≥12 months of continuous follow‐up. We dichotomized adherence at 80%, with ≥24 of 30 days per month considered adherent. We used group‐based trajectory models to estimate monthly adherence patterns and multivariable multinomial logistic regression to determine the association between demographic, SLE and utilization‐related predictors, and the odds ratios (OR) of belonging to a nonadherent versus the adherent trajectory, separately for AZA and MMF. Results: We identified 2, 309 AZA initiators and 2, 070 MMF initiators with SLE. Four‐group trajectory models classified 17% of AZA and 21% of MMF initiators as adherent. AZA and MMF nonadherers followed similar trajectory patterns. African American race (OR 1.67 [95% confidence interval (95% CI) 1.20–2.31]) and Hispanic ethnicity (OR 1.58 [95% CI 1.06–2.35]) increased odds of AZA nonadherence; there were no significant associations between race/ethnicity and MMF nonadherence. Male sex and polypharmacy were associated with lower odds of nonadherence to both medications; lupus nephritis was associated with lower odds of nonadherence to MMF (OR 0.74 [95% CI 0.55–0.99]). Conclusion: Adherence to AZA or MMF over the first year of use was rare. Race, sex, and lupus nephritis were modestly associated with adherence, but the magnitude, direction, and significance of predictors differed by medication, suggesting the complexity of predicting adherence behavior.